A systematic review and meta-analysis of the safety and efficacy of remifentanil and dexmedetomidine for awake fiberoptic endoscope intubation. Issue 14 (9th April 2021) - Tang, Zhi-hang; Chen, Qi; Wang, Xia; Su, Nan; Xia, Zhengyuan; Wang, Yong; Ma, Wu-hua
Abstract: Background: Awake fiberoptic endoscope intubation (AFOI) is the primary strategy for managing anticipated difficult airways. Adequate sedation, most commonly being achieved with remifentanil and dexmedetomidine, is integral to this procedure. This meta-analysis aimed to compare the safety and efficacy of these 2 sedatives. Methods: We conducted electronic searches in Embase, Web of Science, PubMed, Google Scholar, Medline, Springer, and Web of Science with no language restrictions. Studies comparing safety and efficacy between the sole use of remifentanil and dexmedetomidine among patients who underwent AFOI were included. Eight randomized controlled trials, comprising 412 patients, met the inclusion criteria. The primary outcomes were first attempt intubation success rate and incidence of hypoxia. The secondary outcomes were the Ramsay Sedation Scale score at intubation, memory recall of endoscopy, and unstable hemodynamic parameters during intubation. Results: Dexmedetomidine significantly reduced the incidence of hypoxemia during AFOI (risk ratio: 2.47; 95% confidence [CI]: 1.32–4.64]) compared with remifentanil; however, the first intubation success rates were equivalent (risk ratio: 1.12; 95% CI: 0.87–1.46]. No significant differences between the 2 sedatives were found for the Ramsay Sedation Scale score at intubation (mean difference: −0.14; 95% CI: −0.66–0.38) or unstable hemodynamic parameters during intubation (risk ratio: 0.83; 95% CI: 0.59–1.17). Dexmedetomidine reduced memory recall of endoscopy (risk ratio: 1.39; 95% CI: 1.13–1.72). Conclusions: While both remifentanil and dexmedetomidine are effective for AFOI and well-tolerated, dexmedetomidine may be more effective in reducing the incidence of hypoxemia and memory recall of endoscopy. PROSPERP registration number: CRD42020169612.